Foreignness or Processing Fluency? On Understanding the Negative Bias Toward Foreign‐Accented Speakers. Issue 4 (14th June 2020) - Foucart, Alice; Costa, Albert; Morís‐Fernández, Luis; Hartsuiker, Robert J.
Abstract: The extent to which negative bias toward foreign‐accented speakers originates from social categorization (in‐group/out‐group categorization) and/or from processing fluency (ease in processing information) is not clear. Some have argued that accent first induces a social identity effect and that processing fluency later modifies the impact of this effect. Using event‐related potentials (ERPs), this registered report tested this hypothesis, looking at the effect of social categorization and processing fluency on sentence processing. Truth evaluation and the ERP data (N400) did not show significant differences across native and foreign speakers. Debriefing scores on social variables (e.g., status) were lower for foreign speakers, and an exploratory analysis revealed a larger P200 (related to acoustic features) for the native than for the foreign speakers. Hence, foreign speakers were not necessarily perceived as less credible, but accent negatively affected the evaluation of speakers on social variables. Abstract :